A relação da satisfação das condições de caminhabilidade com a qualidade do bairro para caminhada em um município de pequeno porte - Jacob, Juliana Bevilacqua (2018)
The walk can become an enjoyable activity if the public space have characteristics that facilitate the individual to walk through your neighborhood. In the literature, validated instruments of perception and evaluation of walking environments are found to measure the quality of the walking environment. Instruments for perceiving a walking environment were developed by researchers to assess what the pedestrian thinks about the quality of their neighborhood for walking. Instruments of evaluation of the walking environment were developed to measure the quality of the pedestrian infrastructure or the walkability through the determination of the level of service, achieved by technical evaluation. This paper presents the application of an instrument for the perception of the quality of the walking environment (NEWS– Neighborhood Environment Walkability Scale) and the application of a walking environment audit instrument (developed by Nanya, 2016) in a small city. The goal was to identify if there are differences of quality´s perception for walking and the evaluation of the walking environment in different districts of the city. From the statistical tests (kappa = 0.65), it was verified that the general satisfaction of the walking quality of the neighborhood (what the pedestrians think) and the general quality of the neighborhood (audit) has good agreement, where is perceived corresponds to the reality of the general satisfaction of the neighborhood for walking.